Fragmentation of Nimotuzumab for Preparation of 125I-F(ab’)2-Nimotuzumab as a Precursor for Preparing 125I-F(ab’)2-Nimotuzumab-NLS Radiopharmaceutical for Cancer Therapy - R.D. Haryuni; A. Bahtiar; S. Soenarjo; Y. Harahap; A. Mutalib; M. Ramli; S. Hermanto; C.N. Ardiyatno; V.Y. Susilo; D. Haffid (Atom Indonesia, 2014)
Nimotuzumab is an anticancer agent which belongs to the inhibitor group of Epidermal Growth Factor Receptor (EGFR). Thismonoclonal antibody has a relatively high molecular weight which slowspenetration on tumor cells, making it less attractive in imaging kinetics and potentially elicits antibodies responses. Therefore, in this study nimotuzumab was fragmented to form a bivalent antibody [F(ab’)2] and then labeled with 125I to form 125I-F(ab’)2-nimotuzumab which can be used further as a precursor for preparing 125I-F(ab’)2-nimotuzumab-NLS(NLS = nuclear localization sequence) radiopharmaceuticalfor radioimmunotherapy. The aims of this study was to obtain  characteristics of 125I-F(ab’)2-nimotuzumab by comparing with the 125I labeled-intact nimotuzumab (125I-nimotuzumab). This study was initiated by purifying nimotuzumab by mean of dialysis. The purified nimotuzumab was then fragmented by using pepsin. The F(ab')2-nimotuzumab formed was then purified from its by-products which formed in fragmentation process by using a PD-10 column (consisted Sephadex G25). The intact nimotuzumab and its F(ab’)2 fragment were then labeled with the 125I to form 125I-nimotuzumab and 125I-F(ab’)2-nimotuzumab. The radiochemical purity are 98.27 % and 93.24 %, respectively. Stability test results show that, both 125I-nimotuzumab and 125I-F(ab’)2-nimotuzumab are more stable at 4 °C than at room temperature storage and 37 °C.Received: 24 May 2013; Revised: 21 February 2014; Accepted: 28 February 2014